Symbolic Violence against Subordinated Women in Fredrick Backman’s Beartown - Hotman Nasution; Emil Eka Putra (LPPM Universitas Putera Batam, 2022)
This research identified form of symbolic violence in Beartown novel written by Fredrik Backman. The novel displays a social phenomenon where social ideas and expectation constraint women’s life. Symbolic violence helps explaining the phenomenon by looking on how dominant people imposed their view over women for granted. In analyzing the object, the research is equipped with Bourdieu’s theory of symbolic violence. The research is designed in qualitative framework which allows an analysis of interactive variables. In collecting the data, the research applied close reading to the novel. Then, the data is analyzed with latent content analysis. The research found that symbolic violence is exerted mostly through censorship and then euphemism. On censorship, the community preserved desirable view from referring to biased psychological assumption, enforcing dominant view in social, limiting the women’s role, and limiting inclusion of women in sport. On euphemism, symbolic violence is rendered as gentle through gift-debt, familiarity, hospitality, concern, worries, obligation, confidence, and jokes. There is two interesting findings in the analysis. Both forms imposed dominant values which subordinated women in social, education, and sport fields. The second finding is the implication of censorship as frequent used. It displays and confirms the community’s attitude as defensive and protective towards threat on their dominance; including their dominant view